Neurologic Manifestations of Severe Acute Respiratory Syndrome Coronavirus 2 Infection in Hospitalized Patients During the First Year of the COVID-19 Pandemic - Anna M. Cervantes-Arslanian, MD; Chakradhar Venkata, MD; Pria Anand, MD; Joseph D. Burns, MD; Charlene J. Ong, MD; Allison M. LeMahieu, MS; Phillip J. Schulte, PhD; Tarun D. Singh, MD; Alejandro A. Rabinstein, MD; Neha Deo, BS; Vikas Bansal, MBBS, MPH; Karen Boman, BS; et al. (Critical Care Explorations, 2022)
OBJECTIVES:. To describe the prevalence, associated risk factors, and outcomes of serious neurologic manifestations (encephalopathy, stroke, seizure, and meningitis/encephalitis) among patients hospitalized with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. DESIGN:. Prospective observational study. SETTING:. One hundred seventy-nine hospitals in 24 countries within the Society of Critical Care Medicine Discovery Viral Infection and Respiratory Illness Universal Study COVID-19 Registry. PATIENTS:. Hospitalized adults with laboratory-confirmed SARS-CoV-2 infection. INTERVENTIONS:. None. RESULTS:. Of 16,225 patients enrolled in the registry with hospital discharge status available, 2,092 (12.9%) developed serious neurologic manifestations including 1,656 (10.2%) with encephalopathy at admission, 331 (2.0%) with stroke, 243 (1.5%) with seizure, and 73 (0.5%) with meningitis/encephalitis at admission or during hospitalization. Patients with serious neurologic manifestations of COVID-19 were older with median (interquartile range) age 72 years (61.0–81.0 yr) versus 61 years (48.0–72.0 yr) and had higher prevalence of chronic medical conditions, including vascular risk factors. Adjusting for age, sex, and time since the onset of the pandemic, serious neurologic manifestations were associated with more severe disease (odds ratio [OR], 1.49; p < 0.001) as defined by the World Health Organization ordinal disease severity scale for COVID-19 infection. Patients with neurologic manifestations were more likely to be admitted to the ICU (OR, 1.45; p < 0.001) and require critical care interventions (extracorporeal membrane oxygenation: OR, 1.78; p = 0.009 and renal replacement therapy: OR, 1.99; p < 0.001). Hospital, ICU, and 28-day mortality for patients with neurologic manifestations was higher (OR, 1.51, 1.37, and 1.58; p < 0.001), and patients had fewer ICU-free, hospital-free, and ventilator-free days (estimated difference in days, –0.84, –1.34, and –0.84; p < 0.001). CONCLUSIONS:. Encephalopathy at admission is common in hospitalized patients with SARS-CoV-2 infection and is associated with worse outcomes. While serious neurologic manifestations including stroke, seizure, and meningitis/encephalitis were less common, all were associated with increased ICU support utilization, more severe disease, and worse outcomes.